Signaling in Equity Crowdfunding - Ahlers, Gerrit K.C.; Cumming, Douglas; Günther, Christina; Schweizer, Denis (Entrepreneurship Theory and Practice, 2015)
This paper presents a first–ever empirical examination of the effectiveness of signals that entrepreneurs use to induce (small) investors to commit financial resources in an equity crowdfunding context. We examine the impact of venture quality (human capital, social [alliance] capital, and intellectual capital) and uncertainty on fundraising success. Our data highlight that retaining equity and providing more detailed information about risks can be interpreted as effective signals and can therefore strongly impact the probability of funding success. Social capital and intellectual capital, by contrast, have little or no impact on funding success. We discuss the implications of our results for theory, future research, and practice.